PRODUCTION OF AÇAÍ SEEDLINGS UNDER DIFFERENT SHADE LEVELS AND CONTROLLED RELEASE FERTILIZER (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
This study aimed to evaluate the production and quality of açaí seedlings regarding the presence and absence of controlled-release fertilization under different shading levels. The study was conducted at the experimental field of Embrapa - Acre, using a completely randomized design in a 4 x 4 factorial arrangement. The factors included four evaluation periods (60, 120, 180, and 240 days after transplanting) and four shading environments (20%, 30%, 50%, and 75%), along with the presence or absence of controlled-release fertilization. The following variables were analyzed: plant height, stem diameter, number of leaves, dry mass of leaves, stem, root, and total dry mass, as well as the seedling quality index and foliar levels of macro and micronutrients. The growth and development of açaí seedlings are influenced by the evaluation periods, shade environments, and the use of fertilization. Fertilization with controlled-release fertilizer and environments with30% and 50% shading improved the quality of açaí palm seedlings.